Análisis de ingresos y gastos del año 2019 del Comercial Padilla - Miranda Hidalgo, Sonnia María (2020)
The present work consists on the analysis of income and expenses of Commercial Padilla, which is dedicated to the economic activity of wholesale and retail buying and selling of cocoa, located in La Unión parish, Abraham Freire street. The analysis of income and expenses is a subject of great importance, since the reality of a business depends on this, it is also essential to know if the business is generating profits. Based on the information obtained through the observation and interview carried out in the commercial, I determined that the company makes an inadequate record of income and expenses, causing ignorance of the performance of the commercial, likewise it restricts making adequate decisions for the progress of the business and it has prevented a good management of its resources; Due to this, a horizontal and vertical analysis of the Income Statement is essential, this analysis is very important for the owner of the commercial, because it will allow her to know the performance that her company has generated, also to determine which year was most fruitful with respect to the profits and in this way will contribute a lot to decision making, to obtain more economic benefits, knowing how to take advantage of finances. The analysis of some financial reasons will also be carried out, considering the most relevant with respect to the subject of study, which are the profit indicators such as: gross margin, operating margin and net profit margin. These analyzes will facilitate the determination of the profit obtained by the company for each monetary unit sold during the years analyzed.